Prognostic role of left ventricular late gadolinium enhancement (LV-LGE) in patients who received implantable cardioverter defibrillator (ICD) for secondary prevention. (25th November 2020) - Mattesi, G; Baldi, E; Guerra, F; Toniolo, M; Cipriani, A; Cauti, F; Marcantoni, L; Manfrin, M; Lanzillo, C; Savastano, S; Zorzi, A
Abstract: Introduction: LV myocardial fibrosis detected as LGE on cardiac magnetic resonance (CMR) is a predictor of arrhythmic risk in primary prevention both in ischaemic and non-ischaemic cardiomyopathy. However, we still do not know the prognostic role of LV-LGE in patients who suffered cardiac arrest (CA). Purpose: To evaluate the prognostic role of CMR, and in particular of LV-LGE suggesting myocardial scar, in predicting appropriate ICD interventions in secondary prevention patients. Methods: Ninety-seven consecutive patients 1) aged ≥14 years 2) hospitalized for CA because of ventricular arrhythmias from 2009/01/01 3) who underwent/undergoing a CMR within one month from the event 4) who received/receiving an ICD for secondary prevention and 5) with at least 1 year-follow-up, were enrolled for this multicentric study. Results: 97 patients (68 males, 70%), mean age 46±16 years, were enrolled. Seventy-six percent of patients received bystander cardiopulmonary resuscitation (CPR) and ventricular fibrillation (VF) was the first rhythm in 86% of cases. ST elevation was present in 18% of cases at the admission; however, angiography was found negative in 80% of patients. Myocardial oedema and LGE were identified in 26% and 64% of patients respectively. A diagnosis was made in 83.5% of cases, while in the remaining 16.5% CA was considered idiopathic. During a four-year-follow-up, 25% of patients had appropriate ICD therapy (10% of which ATP only). A significant correlation between LGE and appropriate ICD intervention was not found (p=0.89). Conclusions: One fourth of patients who received ICD for secondary prevention had appropriate ICD therapy during a four-year-follow-up. In this setting, LV-LGE does not provide a prognostic value. Funding Acknowledgement: Type of funding source: None